An accounting perspective on intellectual capital - Hussin, Amariah Hanum; Hassan, Haslina; Muda, Salwa (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The accounting profession provides stakeholders with reliable information about the sources of a company’s value. In today’s knowledge-driven economy, intellectual capital (IC) has become a key driver of competitiveness and performance. However, traditional financial reporting often fails to adequately capture and disclose the value of IC, increasing the need for improved accounting practices to better communicate its contribution.